Prohibitin 3 gives birth to a new lateral root primordium. (24th June 2022) - Luo, Le; Xie, Yuanming; Xuan, Wei
Abstract : This article comments on: Li S, Li Q, Tian X, Mu L, Ji M, Wang X, Li N, Liu F, Shu J, Crawford NM, Wang Y. 2022. PHB3 regulates lateral root primordia formation via NO-mediated degradation of AUXIN/INDOLE-3-ACETIC ACID proteins. Journal of Experimental Botany 73, 4034–4045 .